Churchyard and cemetery : tradition and modernity in rural North Yorkshire - Rugg, Julie, 1964- (Manchester University Press ; Distributed in the United States exclusively by Palgrave Macmillan, 2013)
Julie Rugg explores the turbulent social history of churchyards and cemeteries over the last 150 years. Using sites from across rural North Yorkshire, the text examines the workings of the Burial Acts and discloses the ways in which religious politics framed burial management. It presents an alternative history of burial which questions notions of tradition and modernity, and challenges long-standing assumptions about changing attitudes towards mortality in England.